PENGARUH BEBAN KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT EX BATAM INDONESIA - Nora Pitri Nainggolan (JURNAL AKUNTANSI BARELANG, 2018)
This study aims to determine the effect of workload, compensation and work environment on employee performance PT EX Batam Indonesia. The research design used in this research is quantitative research. Population in this research is all employee of PT EX Batam Indonesia operator which amounts to 188 people and the sample used as respondents amounted to 128 people by using slovin formula. Sampling technique with purposive sampling method. Data analysis method consisted of validity test, reliability, classical assumption test, multiple linear regression analysis, coefficient determination test (R2), T test and F test. The results of the study and hypothesis explain that Workload, Compensation and Work Environment partially and simultaneously have a significant effect on Employee Performance.